Recruitment, Selection, and Motivation: Driving Employee Performance AKPAR NHI Bandung - Rika Solihah; Amalia Juliana Monika Intan; Cucu Hodijah (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aimed to examine the influence of recruitment, selection, and motivation on employee performance at AKPAR NHI Bandung, a college of hospitality and tourism in Bandung, Indonesia. A sample of 62 respondents, consisting of 20 academic staff and 42 administrative staff, was selected to participate in the study. Data were collected using questionnaires distributed to the respondents. The findings revealed that both recruitment and selection had a significant positive impact on employee performance. Effective recruitment practices, such as attracting and selecting qualified candidates, were found to be crucial in driving employee performance. Similarly, aligning candidates' qualifications with job requirements through a well-designed selection process positively influenced employee performance. However, no significant relationship was found between motivation and employee performance. These results underscore the importance of implementing effective recruitment and selection strategies to enhance employee performance. Organizations should focus on attracting and selecting highly qualified individuals while ensuring a good fit between candidates and job requirements. Efforts should also be made to foster employee motivation through recognition, career development, and a supportive work environment. The study contributes to the understanding of human resource management practices and their impact on employee performance in the hospitality and tourism industry. The findings highlight the need for strategic human resource management approaches that optimize recruitment and selection processes and address employee motivation.